Epithelial–mesenchymal transition of the eccrine glands is involved in skin fibrosis in morphea. Issue 9 (16th July 2013) - Takahashi, Masayuki; Akamatsu, Hirohiko; Yagami, Akiko; Hasegawa, Seiji; Ohgo, Shiroh; Abe, Masamichi; Iwata, Yohei; Arima, Masaru; Mizutani, Hiroshi; Nakata, Satoru; Matsunaga, Kayoko
Abstract: Morphea is a type of localized scleroderma. It is a skin disease involving the development of fibrosis in the dermis and subcutaneous fat tissue beneath without a visceral lesion, and the cause is still unclear. An involvement of epithelial–mesenchymal transition (EMT) has been reported as a cause of tissue fibrosis, but this was mostly observed in pulmonary and hepatic fibrosis, and the involvement of EMT in a skin disease, morphea, has not been studied . Thus, we analyzed the involvement of EMT in skin fibrosis in morphea patients using pathological techniques. Skin lesions of six morphea patients were analyzed (five female and one male patient). As a control, non‐light‐exposed skin lesions of 11 healthy females were analyzed. Concretely, tissue samples were prepared from these subjects and subjected to immunostaining of transforming growth factor (TGF)‐β1, α‐smooth muscle actin (α‐SMA) and fibronectin, which have been reported to be associated with fibrosis, and Snail1 and E‐cadherin, which are considered to be involved in EMT, and expressions of these were analyzed. In morphea patients, dermal expression of TGF‐β1, α‐SMA and fibronectin, which are involved in fibrosis, was enhanced, and, at the same time, enhanced expression of Snail1 and reduced expression of E‐cadherin, which are involved in EMT, were observed in the dermal eccrine glands. These findings suggested the progression of EMT in the dermal eccrine glands in morphea.